COMPOSITIONS AND FORMATION CONDITIONS OF SILICATE AND SALT MAGMAS FORMING THE GARNET SYENITE PORPHYRIES (SVIATONOSSITES) OF THE CARBONATITE-BEARING MUSHUGAI-KHUDUK COMPLEX, SOUTHERN MONGOLIA - Andreeva I.A.; Kovalenko V.I.; Naumov V.B.; Kononkova N.N. (My University, 2004)
Crystalline and melt inclusions were studied in garnet, diopside, potassium feldspar, and sphene from the garnet syenite porphyry (sviatonossite) of the Mushugai-Khuduk carbonatite-bearing complex in southern Mongolia. Phlogopite, clinopyroxene, albite, potassium feldspar, sphene, wollastonite, magnetite, Ca and Sr sulfates, calcite, fluorite, and apatite were identified among the crystalline inclusions. The melt inclusions were analyzed on an electron microprobe. They were represented by silicate and salt melts and showed homogenization temperatures of 1010-1080°C. Silicate melt inclusions were found in diopside, potassium feldspar, and sphene. They had a variable SiO 2 content, from 56 to 66 wt %, and showed high Na 2O + K 2O (up to 17 wt %), Zr, F, and Cl concentrations. In general the silicate melts were chemically similar to alkali syenite. Salt melt inclusions were found in diopside and garnet. In the course of thermometric experiments, they produced homogeneous quench glasses of sulfate-dominated compositions with an SiO 2 content no higher than 1.3 wt %. These melts are strongly enriched in Ba, Sr, P, F, and Cl. The investigation of the silicate and salt melt inclusions provided evidence for the magmatic genesis of the sviatonossites. These rocks were formed under the influence of the processes of crystallization differentiation and magma separation into immiscible silicate and salt (sulfate) liquids.